What can open access data from India tell us about road safety and sustainable development?. (October 2019) - Jones, Steven; Lidbe, Abhay; Hainen, Alex
Abstract: Transport contributes to socioeconomic development. In the case of rapidly developing and rapidly motorizing societies like India, increased mobility brings an increased burden associated with road crashes and their social and economic consequences. The Sustainable Development Goals explicitly address road safety as necessary to achieving targets related to good health but also as part of the targets leading towards more sustainable cities and communities. We apply Seemingly Unrelated Regression to investigate development-related factors that potentially contribute to differences among urban and rural road crash outcomes using open data sets for 35 states and territories in India. Results indicate that there are relationships among development and crash parameters common to both urban and rural areas. The results indicate different development indicators driving differences in crash outcomes in rural versus urban areas. Study findings are supportive of international efforts to better understand complex relationships among the goals and targets set out in the Sustainable Development Goals and other high-level development-focused declarations such as the New Urban Agenda . It is hoped this paper adds a new perspective on road safety within sustainable development discussions and encourages interdisciplinary research to further explore these relationships across various regions, countries, and contexts.